Fugle-og selundersøkelser på Bouvetøya i desember/januar 1989/90 - Bakken, Vidar (Norsk Polarinstitutt, 1991)
Keywords: Bouvetøya; biologi; fugler; fugleregistreringer; ornitologi; pingviner; seler; zoologi

Thermoregulatory abilities in chicks of the Antarctic Petrel (Thalassoica antarctica) - Bech, Claus; Mehlum, Fridtjof; Haftorn, Svein (Polar Biology, 1991)
We studied the thermoregulatory capacity of Antarctic Petrel chicks, Thalassoica antarctica, breeding in a large colony in Queen Maud Land (71-degrees-53'S, 5-degrees-10'E) on the Antarctic continent. Compared to newly hatched chicks of other birds, those of the Antarctic Petrel are characterized by a relatively high standard metabolic rate (SMR) and thermal conductance. Their metabolic scope is limited, however, being only 1.6 times the SMR, and they consequently depend on parental brooding to maintain T(b). At an age of 11 days the chicks become thermally independent and are left alone in the nest. The chicks keep a relatively high body temperature (> 36-degrees-C) throughout their early development and we found no indication that they normally experience hypothermia. A significant positive relationship between latitude of breeding and SMR of the hatchlings is shown to exist for procellariiform birds. It is suggested that the high SMR found in Antarctic Petrel hatchlings could be a prerequisite for achieving a high growth rate, rather than being of any thermoregulatory significance.
Keywords: Dronning Maud Land; NARE 1984/85; fugler; ornitologi; petreller; zoologi

Foraging economics and performance of polar and subpolar Atlantic seabirds - Croxall, John P; Briggs, Dirk R (Polar Research, 1991)
Keywords: Antarktis; fugler; næring; ornitologi; pingviner; zoologi; økologi

Aspects of the breeding biology of the Antarctic Petrel Thalassoica antarctica and the krill requirement of the chicks, at Svarthamaren in Mühlig-Hofmanfjella, Dronning Maud Land - Haftorn, Svein; Bech, Claus; Mehlum, Fridtjof (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1991)
Keywords: Dronning Maud Land; forskning; fugler; krill; ornitologi; zoologi

Notes on the south polar skua Catharacta Maccormicki breeding at Svarthamaren in Mühlig-Hofmannfjella, Dronning Maud Land - Haftorn, Svein; Bech, Claus; Mehlum, Fridtjof (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1991)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

The density of breeding and non-breeding Antarctic petrels at Svarthamaren, Dronning Maud Land, 1990 - Røv, Nils (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1991)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

Antarktispetrellen: på grensen av det mulige - Sæther, Bernt-Erik (Naturen, 1991)
Keywords: Dronning Maud Land; fugler; ornitologi